(3OjhGf LQjQs - (3LQjQ , LQjQ Hf YWjg Hf MPjag GdNWaj Hf HOQ GdcdHj GdjQHhYj,J (B110 (3g` s ((3HZOGO (B( (3eOjfI GdSdGe s)
(3ChdgG (B:s
(3bGd LQjQ Hf YWjI Hf GdNWai jgLhG dCNWd (B: (3Mi GdZOGI HQGeI GdCWdGdG QSekG JMed Cgdg aCMGdG s
(3BNQgG (B:s
(3aJdaJ PGJ jhe abGd (B: (3Ef JLQ WjQ HCeQ ajg YGajI Ch HGdaQGb abO CMSfJe fGOi gPG BNQ TYQ LQjQ Hf GdMWai s
(3QhGjI eMeO Hf MHjH Yf eMeO Hf RjGO GdCYQGHi Yf YeGQI Hf HdGd Hf LQjQ s
(3ai ChGFd GdbUGFO hHjf GdCHjGJ TQhM hbUGFO GdOjhGf ZjQ eQJHI Ydi GdbhGais
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B119 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B129s
Keywords: (3GdCOHs